2000
DOI: 10.1002/(sici)1097-0347(200001)22:1<64::aid-hed10>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Increased protein nitrosylation in head and neck squamous cell carcinogenesis

Abstract: Background Nitric oxide (NO·) and its metabolic byproducts are implicated in carcinogenesis. We examined a marker of NO·‐species' pathologic protein nitrosylation, nitrotyrosine, during head and neck squamous cell carcinoma (HNSCCa) development. Materials and Methods Paraffin‐embedded tissue samples of normal oral mucosa, squamous hyperplasia/dysplasia, and HNSCCa were immunohistochemically analyzed for staining intensity using an antinitrotyrosine monoclonal antibody, and correlated with retrospective clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Peroxynitrites produced during inflammatory conditions were directly implicated in the promotion of tumor progression via modification and inactivation of different proteins. An association of high peroxynitrite levels with tumor progression was documented for pancreatic cancer, malignant gliomas, head and neck cancer, breast cancer, melanoma, and mesothelioma (17)(18)(19)(20)(21).…”
Section: A Model Of Mdsc-inducible T-cell Tolerancementioning
confidence: 99%
“…Peroxynitrites produced during inflammatory conditions were directly implicated in the promotion of tumor progression via modification and inactivation of different proteins. An association of high peroxynitrite levels with tumor progression was documented for pancreatic cancer, malignant gliomas, head and neck cancer, breast cancer, melanoma, and mesothelioma (17)(18)(19)(20)(21).…”
Section: A Model Of Mdsc-inducible T-cell Tolerancementioning
confidence: 99%
“…Peroxynitrite induces the nitration and nitrosylation of the amino acids cysteine, methionine, tryptophan and tyrosine. Increased levels of peroxynitrite are associated with tumour progression in many types of cancer [49][50][51][52][53][54], which has been linked with T-cell unresponsiveness. …”
Section: Peroxynitritementioning
confidence: 99%
“…In addition, PNT can react directly with cysteine, methionine, and tryptophan (11). A substantial number of studies have demonstrated high levels of nitrotyrosine (NT) in different types of cancer, including pancreatic cancer (12), malignant gliomas (13), head and neck cancer (14), mesothelioma (15), colon carcinoma (16), invasive breast carcinomas (17), melanoma (18,19), and lung cancer (20). In patients with breast cancer, high tumor NT levels were associated with reduced disease-free and overall survival.…”
Section: Introductionmentioning
confidence: 99%